Gender gaps across countries and skills: Supply, demand and the industry structure - Claudia Olivetti; Barbara Petrongolo (Institute for the Study of Labor (IZA), 2011)
The gender wage gap varies widely across countries and across skill groups within countries. Interestingly, there is a positive cross-country correlation between the unskilled-to-skilled gender wage gap and the corresponding gap in hours worked. Based on a canonical supply and demand framework, this positive correlation would reveal the presence of net demand forces shaping gender differences in labor market outcomes across skills and countries. We use a simple multi-sector framework to illustrate how differences in labor demand for different inputs can be driven by both within-industry and between-industry factors. The main idea is that, if the service sector is more developed in the US than in continental Europe, and unskilled women tend to be over-represented in this sector, we expect unskilled women to suffer a relatively large wage and/or employment penalty in the latter than in the former. We find that, overall, the between-industry component of labor demand explains more than half of the total variation in labor demand between the US and the majority of countries in our sample, as well as one-third of the correlation between wage and hours gaps. The between-industry component is relatively more important in countries where the relative demand for unskilled females is lowest.
urn:nbn:de:101:1-201109286283
Keywords: E24; J16; J31; 330; gender gaps; education; demand and supply; industry structure; Lohndifferenzierung; Geschlechterdiskriminierung; Qualifikation; Wirtschaftsstruktur; Welt